Concepções da equipe escolar sobre a gestão escolar e a escola inclusiva - Silva, Daniela Violin da; Costa, Fernanda Aparecida de Souza Corrêa; Capellini, Vera Lúcia Messias Fialho [UNESP]; Carneiro, Relma Urel Carbone [UNESP] (My University, 2012)
Inclusive education is a proposal in which all people are accepted and recognized by their individual characteristics. Thus, this study aimed to investigate the concept of inclusive education and its relation within the democratic management on the early childhood education. Participated in these study educators of two schools in a municipal system school, the data were collected by means of interviews and were analyzed using qualitative approach. Educators participated in the study of two schools in a municipal school, and the data collected by means of interviews and organizes collective actions designed. The survey results suggest that is necessary that the management team is informed and understands the importance of articulating different social segments that can assist special needs of students with disabilities in their needs, promoting thus its development.

Educação Inclusiva é uma proposta na qual todas as pessoas são aceitas e reconhecidas por suas características individuais. Assim, este estudo objetivou investigar a concepção de escola inclusiva e sua relação com a gestão democrática na Educação Infantil. Participaram do estudo educadores de duas escolas de uma rede municipal de ensino, sendo os dados coletados por meio de entrevistas. Para o seu tratamento, foi utilizada abordagem qualitativa e, dos resultados, foram extraídas as inferências mediante a técnica de análise de conteúdo. Os resultados sugerem a necessidade de toda a equipe ser informada e compreender a importância da articulação com os diferentes segmentos sociais para apoiar o aluno com deficiência em suas necessidades, favorecendo, dessa forma, seu desenvolvimento.
Keywords: Inclusive education; Democratic management; Special educational needs; Early childhood education; Educação inclusiva; Gestão democrática; Necessidades educativas especiais; Educação infantil